The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4103/gmit.gmit_1_17
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy and computed tomography imaging in advanced ovarian tumors: A roadmap for prediction of optimal cytoreductive surgery

Abstract: Introduction:Comprehensive staging laparotomy and cytoreductive surgery followed by chemotherapy has been the standard of care in advanced ovarian cancer. Neoadjuvant chemotherapy is an alternative in inoperable advanced cases. To select patients amenable for successful cytoreduction, major determinants including CT imaging and laparoscopy could be of value. There is no general accepted model for selection and reproducibility of techniques are a major challenge due to different clinical practice and complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A 2018 prospective analysis showed a score of less than 8 to have an 85% predictive value for R0 debulking 24 . Even without a formal scoring system, laparoscopic evaluation can be used to confirm histologic subtype and better assess the amount of unresectable disease when CT imaging results are inconclusive 25 …”
Section: Principles Of Surgerymentioning
confidence: 99%
“…A 2018 prospective analysis showed a score of less than 8 to have an 85% predictive value for R0 debulking 24 . Even without a formal scoring system, laparoscopic evaluation can be used to confirm histologic subtype and better assess the amount of unresectable disease when CT imaging results are inconclusive 25 …”
Section: Principles Of Surgerymentioning
confidence: 99%
“…Another study evaluated the importance of PCI-CT in the selection of patients for cytoreductive surgery, whereby patients with a score >15 were recommended neoadjuvant chemotherapy. In this study, the authors concluded that PCI-CT and laparoscopy represent the best option to predict the operability in patients with advanced ovarian cancer 41. More recently, Ahmed et al showed high accuracy of CT imaging, with routine use of a standardized PCI form, for a better comprehensive multiregional analysis.…”
Section: Introductionmentioning
confidence: 70%
“…MDCT-PCI has a good correlation with surgical-PCI in OC (11,28,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). In a prospective study including 85 patients with OC, MDCT and laparoscopy correctly diagnosed PMs in 88.2% and 90.6% of patients, respectively.…”
Section: Role Of Mdctmentioning
confidence: 90%